Efek Bionematisida terhadap Serangan Nematoda Puru Akar Meloidogyne incognita (Koffoid & White) Chitwood pada Beberapa Takaran - Yani Purwanti; Haperidah Nunilahwati; Khodijah Khodijah (Seminar Nasional Lahan Suboptimal, 2018)
Purwanti et al, 2019. Bionematicidal Effects on the Attack of Root-Knot Nematode Meloidogyne incognita (Koffoid & White) Chitwood at Several Doses. pp. 198-205.Biological control by utilizing antagonistic fungi is an alternative control of root-knot nematode (RKN) which does not damage the environment.  Giving organic material to the soil can increase soil fertility and support the success of biological control.  Bionematicides in the form of manure compost enriched with antagonistic fungi at the right dosage are expected to be able to control the attack of root-knot nematodes and increase tomato growth and production.  The aim of the study wass to determine the effect of bionematicide treatment on chicken manure compost enriched with antagonistic fungi from South Sumatra lowland vegetable crops at various doses in controlling the attack of root-knot nematodes on tomato plants. The bionematicide in the form of  chicken manure compost with Aspergillus 2 fungi and Trichoderma  has a high potential in suppressing root-knot nematode attacks.  Increased bionematicidal dose decreases the amount of nodule formed at the roots of tomatoes. Bionematisidal treatment in the form of chicken manure enriched with Aspergillus 2 and Trichoderma fungi at a rate of  300 g  10 - kg of soil produced the lowest amount of the purse on the root with the highest growth and tomato production.